322 Use of the engage for equity framework to longitudinally assess community–academic partnerships - Alex Krist; Emily Zimmerman (Journal of Clinical and Translational Science)
Objectives/Goals: Audience will understand the engage for equity CBPR conceptual framework used to develop our partnership survey. Audience will better understand our survey design and administration process. Audience will understand our initial experiences, community advisory board member responses, and how the process influenced our engagement efforts. Methods/Study Population: The objective of this assessment is to understand how our community partners perceive our engagement efforts. The questionnaire is based on the 12 constructs of the CBPR engage for equity model. We plan on annually assessing impact and refining engagement approaches in response to community partners’ perspectives. Community Advisory Board members and other partners will complete an online survey and participate in a subsequent discussion and planning session about the responses. We anticipate evaluating approximately 400 community partners who collaborate with the Wright Regional Clinical and Translational Science Awards between 2023 and 2030 with a RedCAP survey and discussion. The instrument uses validated questions from a range of engagement instruments to assess context, partnership structure, processes, outputs, and outcomes. Results/Anticipated Results: We hypothesize that both the survey and subsequent discussion about how respondents reacted to answering the questions will improve our ability to track and adapt our community engagement efforts. Discussion/Significance of Impact: Our annual survey is not project specific and using it longitudinally will inform our engagement process to research that aligns with community needs. We anticipate this will help us to guide our research agenda to align with community needs and define impact of our university–community partnership.